From thinking partner to default thinker: GenAI dependency and students’ critical thinking dispositions - S. Sugiyanto (Universitas Ahmad Dahlan, 2026)
The rapid integration of generative artificial intelligence (GenAI) into higher education has raised concerns regarding its potential association with reduced critical thinking engagement, particularly when AI use shifts from intentional assistance to habitual dependency. This study aimed to examine the relationship between Generative AI Dependency (GAD) and critical thinking ability among university students and to investigate whether Need for Cognition (NFC) moderates this relationship. A cross-sectional survey was conducted among 395 Indonesian higher education students, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and multigroup analysis across education level, discipline, employment status, and gender. GAD, operationalized as a higher-order construct comprising cognitive preoccupation, negative consequences, and withdrawal, was negatively associated with critical thinking ability, whereas NFC was positively associated with critical thinking and significantly moderated the relationship between GAD and critical thinking. The negative association between GAD and critical thinking was stronger among vocational students, part-time working students, and STEM students, while the contribution of NFC was stronger among academic-program, full-time, and female students. These findings highlight the importance of educational approaches that promote reflective AI use and strengthen cognitive motivation to support students' higher-order thinking in AI-assisted learning environments.